P331 Productivity loss in patients with inflammatory bowel disease receiving treatment for iron deficiency anaemia: A comparison of ferric maltol and IV iron. (15th January 2020) - Howaldt, S; Jacob, I; Sampson, M; Akriche, F
Abstract: Background: Iron deficiency anaemia (IDA) is common in patients with inflammatory bowel disease (IBD) and can significantly impair health-related quality of life. IDA imposes a substantial economic burden on healthcare payers resulting primarily from increased medical costs and increased rates of hospital admission. IV iron is currently the main treatment for patients intolerant or unsuitable for standard oral iron. Ferric maltol (FM), a stable oral complex of ferric (Fe 3+ ) iron and maltol, is designed to reduce exposure to elemental iron and thus limit gastrointestinal damage. This analysis compares the productivity loss associated with oral FM and IV ferric carboxymaltose (FCM) treatment. Methods: Patients with IBD and IDA (haemoglobin [Hb] ≥8.0 g/dl and ≤11.0 g/dl for women or ≥8.0 g/dl and ≤12.0 g/dl for men, and ferritin <30 ng/ml or ferritin <100 ng/ml with transferrin saturation <20%) were randomised to receive FM (30 mg b.i.d) or IV FCM (as per local SmPC) in an open-label, Phase 3b non-inferiority study. The primary endpoint was Hb responder rate (proportion of patients achieving a ≥2 g/dl increase or normalisation of Hb at week 12); the margin for non-inferiority was 20%. Productivity loss was calculated based on the number of days lost due to iron therapy during the initial 12-week study period. The costs associated with lost productivity were calculated using the human capital approach and based on the average gross income from Germany. Results: 250 patients were randomised: 125 to FM and 125 to IV FCM. The primary non-inferiority endpoint was not met. IV FCM treatment resulted in a loss of patient time because IV administration was limited to a hospital or outpatient setting: 50% of patients treated with IV FCM lost at least one full day due to treatment, with 1 in 15 losing 4–6 days (Table 1). Productivity loss was quantified, with IV FCM treatment associated with losses between €0.00 and €107.21 in 50% of patients, €129.17 and €387.51 in 43% of patients and €516.68 and €775.02 in 7% of patients. FM was administered orally by the patient and did not require any in-hospital treatment, there was no treatment linked productivity loss. Conclusion: IV FCM treatment resulted in productivity loss and disruption to patients' work and family life due to the need for in-hospital/outpatient IV administration. FM treatment had no associated productivity loss as it was administered orally by the patient. FM has none of the indirect costs associated with IV FCM administration and may provide an oral alternative to IV iron in patients with IBD.